Level of Awareness about Thalassemia among Parents of Thalassaemic Children - Muhammad Bilal Ghafoor , Muhammad Saleem Leghari , Ghulam Mustafa , Shazia Naveed (Journal of Rawalpindi Medical College, 2016)
Background: To determine the level of awareness about thalassaemia among parents of thalassaemic children. Methods: In this cross sectional study parents (n=150) of patients suffering from beta thalassaemia major were included. Information was collected on a questionnaire consisting of all the necessary information regarding thalassemia . Eight questions related to knowledge regarding thalassaemia were included. Finally the questionnaires from different parents were analyzed and the result was interpreted. The data was analyzed by SPSS version 16. Results: Sixty percent parents were unaware about the disease, 25% had a little knowledge about the disease and only 15% knew about Thalassemia and its complications. Conclusion: Parental knowledge about thalassaemia was inadequate. It is required to educate not only parents but also general public to create awareness about thalassaemia so that the disease can be eradicated .